Poultry genetics, breeding, and biotechnology - Muir, W. M. (William M.); Aggrey, S. E. (Samuel E.) (CABI Pub., 2003)
This book contains articles on the quantitative and molecular genetics of poultry, the uses of transgenic technology, and genetics of disease resistance and transmission. It is divided into 4 parts: problems and issues associated with poultry breeding (part 1; 6 chapters); breeding strategies and objectives (part 2; 9 chapters); disease resistance and transmission (part 3; 7 chapters); and the use of genomics and bioinformatics in poultry (part 4; 12 chapters).